The Process of Learning Fundamental Football Techniques: A Study of Kicking and Ball Stopping - Kurniawan, Dadang; Hasmyati; Asran (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
Football is a sport that is very popular with students. They play only to seek joy. It turned out that after interviews with students, information was obtained that students felt less interested, afraid, and had leg pain after kicking the ball. The problem formulation of this research is how to improve the learning of basic soccer techniques in kicking and stopping the ball. While the objectives of this study were to describe the improvement of learning the basic techniques of soccer kicking and stopping an interesting ball, several conclusions were obtained from the research as follows: The learning plan for the basic soccer technique of kicking and stopping the ball, as outlined in the syllabus and developed in the Learning Implementation Plan, helps condition students to be active, creative, and fun because students are not bored and pressured to learn. Physical education teachers are expected to develop creativity and innovation. The use of fun and dynamic forms of play Making activity models in physical education learning needs to be improved so that students gain convenience in achieving competence. It is necessary to carry out classroom action research for learning other physical education materials so that the goal of improving the quality of physical education learning can be achieved.